Hospital Waste Management Practices: Explanation from Medical Personnel - Suriati, Deraman; Lee, Khai Loon; Puteri Fadzline, Muhamad Tamyez (Penerbit Universiti Malaysia Pahang, 2021)
Today, the healthcare industry has become more important with the increasing number of hospitals due to the rise of patients. This signifies the world is facing more critical issues towards hospital waste due to its impact on the environment. The increase of waste generation from the hospital is not only to the environment but to an organisation such as cost of disposal. Current research fails to provide a manager behaviour view on the solution to reduce waste from their organization. Thus, this study explores the current hospital waste practices at the hospital, to examine depth understanding of recycling factor behaviour among medical personnel and the impacts from recycling hospital waste. This study used the semi-structured interview with hospital managers to address The result shows, respondents are willing to recycle hospital waste with factors such as government support, top management involvement through providing training, awareness, knowledge, facilities and incentives. This study will contribute to both bodies of knowledge and practice among hospital managers.